SISTEM ZONASI DAN KETIMPANGAN MUTU PENDIDIKAN: TELAAH KONSEP KEADILAN DALAM ISLAM : TELAAH KONSEP KEADILAN DALAM ISLAM - Al Mubarok, Moh Safik (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
The zoning system policy in Indonesian education was introduced with the spirit of equal access, providing opportunities for students from various backgrounds to receive an education in public schools. However, in its implementation, this system has actually given rise to new problems related to inequality in educational quality. This study aims to analyze how the zoning system affects the gap in educational quality at SMA Negeri 77 Jakarta and examines it from the perspective of Islamic justice. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation. Research informants included teachers, students, and parents. All data were analyzed descriptively qualitatively to describe objective conditions in the field, then interpreted using the principles of justice in Islam. The results show that the zoning system has not fully created justice in educational quality. There are disparities in students' academic readiness, learning character, and family support that influence the teaching and learning process. Students enrolled in the zoning pathway tend to face adaptation difficulties, fall behind academically, and receive less support for home-based learning. This inequality stems not only from the students themselves but also reflects a system that treats disparate conditions uniformly. From an Islamic perspective, justice is not about equal treatment, but rather about giving according to the needs and capacities of each individual. Therefore, the zoning system needs to be complemented by affirmative policies such as remedial programs, character development, and collaborative partnerships between schools and parents. Fair education, according to Islam, is not only about providing access but also about ensuring meaningful and equitable learning processes and outcomes for all students.